Hysteroscopy as a standard procedure for assessing endometrial lesions among postmenopausal women - Ribeiro, Camila Toffoli; Rosa-e-Silva, Júlio César; Silva-de-Sá, Marcos Felipe; Rosa-e-Silva, Ana Carolina Japur de Sá; Poli Neto, Omero Benedicto; Reis, Francisco José Candido dos; Nogueira, Antonio Alberto (São Paulo Medical Journal, 2007)
CONTEXT AND OBJECTIVES: Endometrial cancer is the most prevalent type of malignant neoplasia of the genital tract. The objective of this study was to calculate the sensitivity, specifi city, accuracy and positive and negative predictive values for diagnostic hysteroscopy, in comparison with histopathological tests, for all lesions of the endometrial cavity. DESIGN AND SETTING: Retrospective descriptive study at the public tertiary-level university hospital of Faculdade de Medicina de Ribeirão Preto, Universidade de São Paulo. METHODS: Diagnostic hysteroscopy was indicated in the following instances: endometrial thickness > 4 mm in asymptomatic patients; postmenopausal bleeding; and irregular endometrium or endometrium difficult to assess from ultrasound, with or without vaginal bleeding. Ultrasound evaluations were carried out no more than three months prior to hysteroscopy. RESULTS: There were 510 patients, with a mean age of 61.1 ± 2.0 years and mean time elapsed since the menopause of 12.7 ± 2.5 years. Endometrial biopsies were performed on 293 patients (57.5%). Histopathological analysis showed that 18 patients presented endometrial carcinoma or typical or atypical hyperplasia, and none of them presented endometrial thickness of less than 8 mm. No signifi cant differences were found between the median thicknesses of the various benign lesions (p > 0.05). In our data, the sensitivity, specifi city, accuracy and positive and negative predictive values for cancer or hyperplasia were 94.4%, 97.0%, 96.8%, 68% and 99.6%, respectively. CONCLUSIONS: Our results suggest that hysteroscopy is valuable as a diagnostic tool for malignant/hyperplastic and benign lesions, except for submucous myomas, for which the sensitivity was only 52.6%.